The Gaze Communications Between Dogs/Cats and Humans: Recent Research Review and Future Directions - Koyasu, Hikari; Kikusui, Takefumi; Takagi, Saho; Nagasawa, Miho (Frontiers in Psychology, 2020)
Dogs (Canis familiaris) and cats (Felis silvestris catus) have been domesticated through different processes. Dogs were the first domesticated animals, cooperating with humans by hunting and guarding. In contrast, cats were domesticated as predators of rodents and lived near human habitations when humans began to settle and farm. Although the domestication of dogs followed a different path from that of cats, and they have ancestors of a different nature, both have been broadly integrated into—and profoundly impacted—human society. The coexistence between dogs/cats and humans is based on nonverbal communication. This review focuses on “gaze,” which is an important signal for humans and describes the communicative function of dogs’ and cats’ eye-gaze behavior with humans. We discuss how the function of the gaze goes beyond communication to mutual emotional connection, namely “bond” formation. Finally, we present a research approach to multimodal interactions between dogs/cats and humans that participate in communication and bond formation.